Internationalisation strategy for education in the 21st century - John Saee (Journal of Business Economics and Management, 2004)
There has been a sea change in the world economy with perceived far‐reaching consequences on all aspects of human civilization. This dramatic transformation is largely precipitated by the phenomenon of globalization.